Effects of population spatial redistribution on vegetation greenness: A case study of Chongqing, China. (May 2022) - Lu, Dan; Wang, Yahui; Yang, Qingyuan; Wang, Zhanpeng; Lin, Aiwen; Tang, Yuxue; Li, Yuanqing
Graphical abstract: Highlights: Human activities played a dominant role in the vegetation restoration. Population emigration made the greatest contribution to vegetation change (62.47%). The effect of population migration on vegetation varied with elevation. The Grain-for-Green program had a positive effect on vegetation. Abstract: With the continuous increase in urbanization and non-farm wages, many rural labor forces have transferred to urban areas, significantly changing the population distribution and affecting vegetation restoration and ecological environment improvement. This study analyzed the spatiotemporal patterns of vegetation in Chongqing from 2000 to 2018 based on the MODIS EVI dataset, and 862 samples were randomly selected to quantitatively analyze the contribution degree of population emigration to vegetation greenness by using the multivariate linear regression model under the conditions of controlling climate, topography, and policy factors. The results showed that the vegetation in Chongqing presented a significant improvement trend. Human activities played a dominant role in the vegetation restoration in Chongqing from 2000 to 2018. The contribution of population spatial redistribution to vegetation changes was 62.47%, and the contributions gradually decreased with increasing elevation, which were 73.90%, 45.02%, and 17.87% in the low, medium, and high altitude areas, respectively. Furthermore, the Grain-for-Green program significantly affected vegetation variation, and the project had the greatest ecological benefits in medium-altitude areas.